Penerapan Pendekatan Hypnoteaching Dalam Pembelajaran Matematika Pada Siswa Kelas VII SMP Negeri 7 Kerinci - Eline Yanty Putri Nasution; Yumna Eriksani; Rahmi Putri (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2023)
Hypnoteaching comes from two words hypno and teaching. Hypnoteaching is a unique and imaginative learning method in which students follow the learning process in a fresh condition and are ready to accept the subject matter. This research is a quasi-experimental study with an inequivalent control group design. The subjects of this study were selected by cluster random sampling obtained by Class VII A which consisted of 22 people who applied the Hypnoteaching approach and the Control Class was Class VII B which consisted of 20 people who applied direct learning. The data collection method used is the method of documentation, observation and learning achievement tests. From the results of the research and discussion, it can be concluded that: 1) student learning outcomes in the experimental class using the Hypnoteaching learning approach obtained an average value of 84.58 and categorized as very good, 2) student learning outcomes in the control class that did not use the Hypnoteaching learning approach were obtained the average score is 73 and categorized as good, and 3) there are differences in the student mathematical learning outcomes that use the Hypnoteaching approach and those that do not use the Hypnoteaching approach in class VII SMPN 7 Kerinci.